Metalized Plastic Waste Fiber Effects on Green Concrete Beams Mechanical Performance - Hamed Safayenikoo (Shock and Vibration)
In a year, millions of forms of plastic are produced, and approximately, half of the generated plastics are used once only. Incorrect and insufficient management of these waste materials causes adverse effects on the nature of the soil, water, humans, and animals’ life. One type of waste plastic is metalized plastic waste (MPW), which is used mainly in different types of food packaging productions, and there is no appropriate technology for reusing it all over the world. In this paper, the effect of MPW as a fiber by 0.5% and 1% on compressive, flexural load capacity, and toughness of green concrete containing 7.5% and 15% silica fume or natural zeolite in Oman Sea tidal zone environment at 28, 90, and 180 days was investigated. The results indicate that by adding the MPW fiber, the compressive strength and maximum flexural load capacity of green concrete were decreased 25% and 15%, respectively. Meanwhile, the effect of MPW fiber on concrete containing 15% silica fume was greater than 7.5% silica fume concrete. Flexural toughness of natural zeolite concrete containing 0.5% MPW fiber was up to 510.9% greater than the observed one. Moreover, the toughness of green concrete containing 1% MPW fiber and zeolite was up to 35% greater than 0.5% MPW concrete. Meanwhile, the effect of MPW fiber on flexural toughness of concrete containing 15% natural zeolite was greater than 7.5% natural zeolite concrete.